Gastroschisis in Ontario, Canada: 2012–2018. Issue 14 (19th April 2021) - Bourque, Danielle K.; Meng, Lynn; Dougan, Shelley; Momoli, Franco; Riddell, Catherine; Walker, Mark; Armour, Christine M.
ABSTRACT: Background: Gastroschisis is a congenital anomaly of the abdomen in which the intestines are found outside of the body at birth. While no clear causative factors have been identified, it is strongly associated with young maternal age. Other reported associations include low maternal socioeconomic status, low maternal body mass index (BMI), and smoking. Methods: This is a retrospective review of epidemiologic data relating to cases of gastroschisis in Ontario from 2012‐2018 in the Better Outcomes Registry & Network (BORN) Ontario database, which is the province's prescribed maternal‐newborn registry. We describe the epidemiology of gastroschisis in Ontario with respect to birth prevalence, maternal age, health, exposures, and geography. Results: The birth prevalence of gastroschisis is 2.31 cases/10, 000 births. There was no apparent change in birth prevalence over the study period and there was no difference between male and female infants. Gastroschisis was associated with younger maternal ages and was inversely correlated with maternal BMI. Gastroschisis was associated with first completed pregnancy. Maternal diabetes was associated with a lower birth prevalence of gastroschisis than average. Mothers of babies with gastroschsis were more likely to report use of tobacco, alcohol, and drugs during pregnancy than those without gastroschisis, with marijuana use showing the largest increase in birth prevalence of gastroschisis. Mothers living in rural areas were more likely to have a baby with gastroschisis than those in urban centers, even after controlling for maternal age. Conclusions: This Ontario registry study reveals that mothers with babies with gastroschisis are more likely to be young and thin, live in rural areas, and report prenatal smoking, alcohol use, and drug use than women whose pregnancies do not have gastroschsis.